Virtue Existential Career Model: A Dialectic and Integrative Approach Echoing Eastern Philosophy - Liu, Shu-Hui; Hung, Jui-Ping; Peng, Hsin-I; Chang, Chia-Hui; Lu, Yi-Jen (Frontiers in Psychology, 2016)
Our Virtue Existential Career (VEC) model aims at complementing western modernism and postmodernism career theories with eastern philosophy. With dialectical philosophy and virtue-practice derived from the Classic of Changes, our VEC theoretical foundation incorporates merits from Holland typology, Minnesota Theory of Work Adjustment, Social Cognitive Career Theory, Meaning Therapy, Narrative Approach Career Counseling, and Happenstance Learning Theory. While modernism considers a matched job as an ideal career vision and prefers rational strategies (controlling and realizing) to achieve job security; postmodernism prefers adapting and appreciating strategies toward openness and appreciates multiple possible selves and occupations, our VEC model pursues a blending of security and openness via controlling-and-realizing and appreciating-and-adapting interwoven with each other in a dialectical and harmonious way. Our VEC counseling prototype aims at a secular goal of living on the earth with ways and harmony (安身以法以和) and an ultimate end to spiral up to the wisdom of living up to the way of heaven (天道) with mind and virtue (立命以心以德). A VEC counseling process of five major career strategies, metaphorical stories of qian and kun, and experiential activities are developed to deliver VEC concepts. The VEC model and prototype presented in this research is the product of an action research following Lewin’s (1946) top-to-down model. Situated structure analyses were conducted to further investigate the adequacy of this version of VEC model and prototype. Data from two groups (one for stranded college graduates and the other for growing college students) revealed empirical supports. Yang type of career praxes tend to induce actualization, which resulting in realistic goals and concrete action plans; yin type of career praxes tend to increase self-efficacy, which resulting in positive attitude toward current situatedness and future development. Acceptance and dialectic thinking often result from yin-yang-blending career praxes. Growing developers benefit from a strategy sequence of yang-yin-synthesized; stranded developers from a strategy sequence of yin-yang-synthesized. Our contributions and limitations are discussed in the context of developing indigenous career theories and practices for a globalized and ever-changing world.